(untitled) (Agora for Physical Education and Sport, 2022)
For the enlightened Argentines of the late nineteenth and early twentieth centuries, consolidating public education was a matter of utmost importance. In this context, Europe, but especially Spain, offered certain progressive intellectual premises that the Argentine ruling elite looked upon with pleasure. This context made possible a pedagogical renewal movement, which paved the way for almost a century later, the Spanish model called Sports Initiation, monopolized the theoretical field, managing the practice and definitively conditioning the discipline, instituting its curricular concern as pedagogical knowledge. This text establishes a look that articulates history with the present, to think about the influence of enlightened Spanish thought for the current pedagogicalization and sportsmanship of Physical Education.